Combining complement fixation and luminol chemiluminescence for ultrasensitive detection of avian influenza A rH7N9. Issue 6 (10th February 2016) - Li, Man; Shi, ZhuanZhuan; Li, ChangMing; Yu, Ling
Abstract : A luminol chemiluminence system was applied in the complement fixation test for detection of rH7N9 in the range of 0.25 fg mL −1 –25 ng mL −1 . Abstract : The complement fixation test (CFT) is a serological test that can be used to detect the presence of either a specific antibody or antigen to diagnose infections. In a conventional CFT, the assay result is determined by observing the clarity of the reaction solution or the sediment of red cells by the naked eye. Although the assay conditions are thereafter simplified, the sensitivity of the assay would be sacrificed due to the limitation of bulk observation. Inspired by the forensic scientists to examine blood at the scene of the crime, we rationally argued that the luminol chemiluminescence (CL) reaction could be applied in the CFT to sense physiological complement-mediated haemolytic phenomena for sensitive protein detection. The combination of the CFT and the luminol CL system was demonstrated in detection of rH7N9, a recombinant avian influenza virus protein. The testing can be accomplished within 2.5 h and the linear detection range covers 0.25 fg mL −1 to 25 ng mL −1 . The feasibility of the CL based CFT in assaying a real biopsy was successfully demonstrated by specifically detecting rH7N9 and the carcinoembryonic antigen (CEA) in human serum. This new type of protein detection approach inherits the beauty of complement-mediated assay, such as being fast, and no protein immobilization, blocking and washing. In addition, the participation of luminol CL enables us to quantitatively analyse the intensity of a haemeolysis process, ameliorating the limitation of bulk observation in traditional CFT. It is anticipated that the luminol CL-CFT assay would be particularly suitable for investigation of small molecules, toxins, and short peptides.